Edukasi Kesehatan Tentang Penyakit Menular Seksual pada Wanita Usia Subur di Wilayah Kerja Puskesmas Pekkabata - Safitry, Rusni; Niar, Niar (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2024)
Introduction: Reproductive health is one of the global health challenges that needs to be considered in everyday life. Issues related to reproductive health are closely related to biological health problems in women of childbearing age (WUS).Sexually Transmitted Infections or often known by the abbreviation STI are diseases caused by infections that can be contracted through sexual contact. STIs, also known as sexually transmitted diseases, can be spread through bodily fluids, such as sperm, blood or other fluids. In an effort to avoid sexually transmitted infections, the government is implementing safe sexual behavior, including the use of condoms, which are considered the best contraceptive method for preventing STIs. Objective: This Community Service aims to provide education to Women of Childbearing Age about Sexually Transmitted Diseases. Method:Health education activities regarding sexually transmitted diseases in women of childbearing age are carried out through lectures and discussions.  The activity will be held on October 25 2024. Participants in this outreach activity are women of childbearing age at Posyandu Mekar Jaya, Darma sub-district, Pekkabata Community Health Center Working Area, totaling 20 people. Health Education presents material about the meaning of sexually transmitted infections, causes, symptoms, prevention, treatment and screening for sexually transmitted infections for 30 minutes. Result: The results of the report show that the participants' knowledge in understanding the problem of sexually transmitted infections has increased quite significantly. In this activity, the participants were also very enthusiastic in receiving the material presented Conclusion: The conclusion of this research is increased knowledge and understanding of women of childbearing age about the meaning of sexually transmitted infections, symptoms of sexually transmitted infections, causes of sexually transmitted infections, prevention of sexually transmitted infections, as well as treatment and screening by visiting health workers for consultation.